A systems biology approach for studying neurodegenerative diseases. Issue 7 (July 2020) - Lam, Simon; Bayraktar, Abdulahad; Zhang, Cheng; Turkez, Hasan; Nielsen, Jens; Boren, Jan; Shoaie, Saeed; Uhlen, Mathias; Mardinoglu, Adil
Highlights: Biotechnological advancements in the late 20th century have aided NDD research. Blood, cerebrospinal fluid, stem cells, and cerebral organoids are alternatives to postmortem brain tissue. Public resources such as the HPA Brain Atlas and Accelerating Medicines Partnership-AD may accelerate NDD research. Heterogeneity of NDDs causes clinical trial failure and can be addressed using systems biology. We recommend a philosophical shift away from the umbrella terms for AD and PD. Abstract : Neurodegenerative diseases (NDDs), such as Alzheimer's (AD) and Parkinson's (PD), are among the leading causes of lost years of healthy life and exert a great strain on public healthcare systems. Despite being first described more than a century ago, no effective cure exists for AD or PD. Although extensively characterised at the molecular level, traditional neurodegeneration research remains marred by narrow-sense approaches surrounding amyloid β (Aβ), tau, and α-synuclein (α-syn). A systems biology approach enables the integration of multi-omics data and informs discovery of biomarkers, drug targets, and treatment strategies. Here, we present a comprehensive timeline of high-throughput data collection, and associated biotechnological advancements and computational analysis related to AD and PD. We hereby propose that a philosophical change in the definitions of AD and PD is now needed. Teaser: A timeline of high-throughput omics data for neurodegeneration research shows that systems biology approaches have promising ability for the study of cellular and metabolic changes in Alzheimer's and Parkinson's diseases, challenging the way researchers should define these diseases.